Current Immunotherapies for Sarcoma: Clinical Trials and Rationale. (14th September 2016) - Mitsis, Demytra; Francescutti, Valerie; Skitzki, Joseph
Abstract : Sarcoma tumors are rare and heterogeneous, yet they possess many characteristics that may facilitate immunotherapeutic responses. Both active strategies including vaccines and passive strategies involving cellular adoptive immunotherapy have been applied clinically. Results of these clinical trials indicate a distinct benefit for select patients. The recent breakthrough of immunologic checkpoint inhibition is being rapidly introduced to a variety of tumor types including sarcoma. It is anticipated that these emerging immunotherapies will exhibit clinical efficacy for a variety of sarcomas. The increasing ability to tailor immunologic therapies to sarcoma patients will undoubtedly generate further enthusiasm and clinical research for this treatment modality.